The Search for Job Satisfaction: A Survey of Alabama Policing - Carlan, Philip E. (American journal of criminal justice, 2007)
This study examines police job satisfaction and its association with general occupational attraction. Police officers from sixteen municipal departments (n = 1,114) across one southern state (Alabama) were found to possess moderate-high overall job satisfaction, with regression analysis supporting the conclusions of prior studies that demographics are of little value to understanding job satisfaction. The findings convey that 25% of job satisfaction variance can be explained from six variables (in order of importance): social contribution, pay, adventure/excitement, autonomy, peer respect, and job security. The importance of benefits and community respect was unsupported, as were partner and special operation assignments. The author concludes that a great portion of police satisfaction hinges on the realization of work environment expectations, and that departments must proactively construct policies to enhance fulfillment of officer aspirations.